EFISIENSI PEMASARAN CABAI MERAH LAHAN PASIR MELALUI PASAR LELANG DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , EBBAN BAGUS KUNTADI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objectives of the research are : 1 ). Knowing income of sand farm red chilli farmer that utilize auction market. 2 ) Knowing marketing efficiencies of sand farms red chilli 3 ) Knowing factors that influence farmerâs decision to choose auction market. Sampling method in this research used by multistage random sampling method. The first objective analyzed by use cost and income analysis and hypothesis test is ude t test for independent samples, meanwhile second objective analyze with marketing margin analysis and monopoly index (MPI) and the third objective being answered by use of model binary logistic's regression . The result of this research are that income and sell price that selling through auction market overbids than sell price and income that don't pass through auction market. Average income through auction market is IDR 249,678,008 / hectare whereas average income not through auction is IDR 187,732,909 / hectare. Farmerâs income and sell price between farmer that utilize auction market and farmer that don't utilize auction market are signifikan different on level 1%. Marketing margin of red chili through auction market as big as IDR13,150 where assesses it is smaller than marketing margin that doesn't pass through auction market which is each of IDR 14,650